EVALUASI PENERAPAN SANITASI LOKASI, BANGUNAN, KARYAWAN, DAN PERALATAN PRODUKSI TEH HIJAU (Studi Kasus Di PT Rumpun Sari Kemuning) - , SHODIQ JALU TANUGAL ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT Rumpun Sari Kemuning is an industrial process to be green tea tea shoots. Because green tea is a food product, it is to produce quality food and minimize environmental pollution, food industry need to apply good principles of food processing and environmental management. Management of the food is good and right is basically managing the food based on the principles of the principles higyene and food sanitation. With the management and application of sanitary food is good and right will produce a quality food, clean, healthy, and safe. This thesis aims to determine the location of the application of sanitary, building, labor, and equipment production conducted by PT. Rumpun Sari Kemuning, identify deviations from the implementation of sanitation programs, and formulate solutions as well as a good way of handling to prevent contamination, either from the location, building, employees and production equipment to improve the safety of green tea products. Based on the guidance of the Minister of Industry in 2010 CPPOB sanitation implementation of green tea processing in PT. Rumpun Sari Kemuning include locations sanitation, buildings, employees and production equipment acquired suitability for 85.7%, 66.7%, 66.7%, and 78.5%. Sanitary irregularities within the scope of the production process is concluded with Ishikawa diagram, which in general is the lack of awareness of hygiene, a lot of infrastructure building that does not fit the rules, employees are not using work equipment, machinery and equipment there are a few surface is chipped. Appropriate repair solutions include cleaning and supervision perform effectively and regularly to the building and the environment as well as production equipment, making the design of buildings and facilities to meet the hygienic requirements that have been defined, well implemented hygiene behaviors, and provide decisive action to employees who offense the rule.